Batch, column and thermodynamic of Pb(II) adsorption on xanthated rubber (Hevea brasiliensis) leaf powder - Wan Mohd Khalir, Wan Khaima Azira (Asian Network for Scientific Information, 2012)
Rubber (Hevea brasiliensis) leaf powder was modified by xanthation process and its potential in removing toxic Pb(II) ion from aqueous solutions was investigated in batch and column experiments. Pb(II) adsorption efficiency was found to be affected by several physicochemical parameters such as adsorbent dosage, shaking rate and temperature. The optimum adsorbent dosage was found to be at 0.02 g with more than 80% Pb(II) removal. The amount of Pb(II) adsorbed (mg g-1) increased with increasing shaking rate but decreased with increasing adsorbent dosage and temperature. Thermodynamic parameters such as enthalpy change (ΔH°), free energy change (ΔG°) and entropy change (ΔS°) were computed and Pb(II) adsorption process was found to be exothermic. Fixed-bed column fitted well the Thomas and Yoon-Nelson models with correlation coefficients of R2>0.96.